Dynamic sliding mode control based on a full-order observer: Underactuated electro-mechanical system regulation - Ordaz, Patricio; Romero-Trejo, Hugo; Cuvas, Carlos; Sandre, Omar (Zielona Góra: Uniwersytet Zielonogórski)
This paper concerns the synthesis of a nonlinear robust output controller based on a full-order observer for a class of uncertain disturbed systems. The proposed method guarantees that, in finite time, the system trajectories go inside a minimal neighborhood ultimately bounded. To this end, the attractive ellipsoid method is enhanced by applying the dynamic sliding mode control performance properties. Furthermore, in order to guarantee the stability of the trajectory around the trivial solution in the uniform-ultimately bounded sense, the feasibility of a specific matrix inequality problem is provided.
Keywords: output feedback and observers; sliding mode control; attractive ellipsoid method; uncertain systems; nonlinear systems